Dihydrotanshinone I Specifically Inhibits NLRP3 Inflammasome Activation and Protects Against Septic Shock In Vivo - Ziying Wei; Ziying Wei; Xiaoyan Zhan; Xiaoyan Zhan; Kaixin Ding; Kaixin Ding; Guang Xu; Wei Shi; Lutong Ren; Lutong Ren; Zhie Fang; Tingting Liu; et al. (Frontiers in Pharmacology, 2021)
The abnormal activation of the NLRP3 inflammasome is closely related to the occurrence and development of many inflammatory diseases. Targeting the NLRP3 inflammasome has been considered an efficient therapy to treat infections. We found that dihydrotanshinone I (DHT) specifically blocked the canonical and non-canonical activation of the NLRP3 inflammasome. Nevertheless, DHT had no relation with the activation of AIM2 or the NLRC4 inflammasome. Further study demonstrated that DHT had no influences on potassium efflux, calcium flux, or the production of mitochondrial ROS. We also discovered that DHT suppressed ASC oligomerization induced by NLRP3 agonists, suggesting that DHT inhibited the assembly of the NLRP3 inflammasome. Importantly, DHT possessed a significant therapeutic effect on NLRP3 inflammasome–mediated sepsis in mice. Therefore, our results aimed to clarify DHT as a specific small-molecule inhibitor for the NLRP3 inflammasome and suggested that DHT can be used as a potential drug against NLRP3-mediated diseases.